Зниження енерговитрат диспергування в пульсаційному гомогенізаторі рідких продуктів - Ковальов, Олександр Олександрович; Самойчук, Кирило Олегович; Паляничка, Надія Олександрівна; Kovalyov, Oleksandr; Samoichuk, Kyryl; Palianychka, Nadiia (Запоріжжя : 2024, 2024)
UA: В статті проаналізовано конструкції пульсаційних гомогенізаторів рідких продуктів. Результати аналізу дозволяють стверджувати, що для забезпечення якості продукту згідно вимог технологічної документації конструктивні особливості прототипу та аналогу передбачають багаторазову обробку продукту протягом однієї операції. Це призводить до підвищення енергетичних витрат диспергування та зниження продуктивності гомогенізаторів. Запропоновано корисну модель, в якій обґрунтовано доцільність використання 3…5 поршнів-ударників, замість одного. Доведено, що впровадження вдосконалення забезпечить зниження енергетичних витрат диспергування за рахунок підвищення інтенсивності впливу поршнів на продукт протягом одного циклу. Обґрунтовано, що за рахунок збільшення кількості поршнів-ударників можливо досягти підвищення продуктивності обладнання, що досягається за рахунок зниження кратності обробки емульсії в гомогенізаторі. EN: The high share of energy costs in the balance of the cost of food processing in Ukraine forces scientists to look for ways to increase the energy efficiency of processing enterprises, in particular, the milk processing industry. Dispersion is one of the technologically mandatory, but at the same time, the most energy-consuming operations of the technological process. The percentage share of energy consumption for carrying out this operation alone is 25-40% in the total energy balance of processing dairy products. The results of prospective studies indicate that it is possible to achieve a 6-fold reduction in energy costs for dispersion by developing and implementing structures that ensure the intensification of the impact on the product. One example of such a design is a group of pulsating homogenizers for processing liquid products. When they work, the product passes from the upper to the lower cavity of the cylinder, in which a pistonimpactor is installed on the rod, due to which the reciprocating movement of the piston and the effect on the product of the jets formed in the area of the through holes of the piston are ensured. The article analyzes the designs of the analogue and prototype of the useful model. The obtained results allow us to state that the design features of the considered useful models cause high values of energy costs when a product is affected by one impactor piston and cause a decrease in productivity due to a large number of product processing cycles in one technological operation. The proposed design solves the problems of high dispersion energy costs and low productivity by installing additional impact pistons, the number of which should be within 3...5. The proposed improvement will ensure the intensification of the effect of the working bodies of the homogenizer on the product, which will lead to a decrease in the energy costs of the dispersion process and ensure the production of a product with a uniform dispersion composition. Productivity will be increased by reducing the frequency of product processing in the homogenizer.
Reduced energy vitrate dispersion in pulsation homogeniser of rare products
Keywords: пульсаційний; кратність обробки; поршень; амплітуда; шток; знежирене молоко; диспергування; вершки; pulsating; multiplicity of processing; piston; amplitude; stem; milk; dispersion; cream